PHYSICAL ACTIVITY OF WOMEN AND MEN IN THE TIME OFF WORK - Czarnecki, D.; Skalski, D. W.; Kreft, P.; Kaszowska, M.; Nikolenko, O. (Rehabilitation and Recreation, 2023)
Free time performs many important functions at every stage of human development, although it is usually devoted to rest and self-realization. In the literature on the subject, you can find numerous definitions of free time, and their common denominator is the impact on the holistic development of a human being. One of the key functions of free time is rest and recreation, and thus – physical activity. Regular physical activity determines the quality and length of a person's life. Properly selected activity also enriches the intellectual sphere and allows you to maintain a balance between the condition of the body and the state of mind. It contributes to a better psychophysical condition, as well as to better well-being. Physical activity is extremely important for the proper development of an individual, especially when modern society is exposed to a sedentary lifestyle. Playing sports and systematic outdoor movement not only brings many benefits to the individual, but also to society as a whole. A healthy society lives longer, is more productive and, above all, is aware of a healthy lifestyle. Physical activity is therefore an important factor in shaping health, healthy habits, but also valuable spending free time. Despite the currently growing involvement of the society in physical culture, the statistics are still unsatisfactory. Only every seventh Pole (16.1%) aged 15–69 meets the standards for the level of physical activity in free time recommended by the World Health Organization. Among men (18.9%) the share of people meeting WHO recommendations is slightly higher than among women (13.4%). Many studies emphasize that men play sports more often than women, although in many situations they are more organized and systematic and taking care of their health. On the other hand, outside of work, they are more burdened with household chores. The growing awareness of the role of physical activity in the prevention of civilization diseases, as well as differences in health care depending on gender, inspired the undertaking of this research.